Benign descriptors and ADNEX in two‐step strategy to estimate risk of malignancy in ovarian tumors: retrospective validation in IOTA5 multicenter cohort. (12th January 2023) - Landolfo, C.; Bourne, T.; Froyman, W.; Van Calster, B.; Ceusters, J.; Testa, A. C.; Wynants, L.; Sladkevicius, P.; Van Holsbeke, C.; Domali, E.; Fruscio, R.; Epstein, E.; et al.
ABSTRACT: Objective: Previous work has suggested that the ultrasound‐based benign simple descriptors (BDs) can reliably exclude malignancy in a large proportion of women presenting with an adnexal mass. This study aimed to validate a modified version of the BDs and to validate a two‐step strategy to estimate the risk of malignancy, in which the modified BDs are followed by the Assessment of Different NEoplasias in the adneXa (ADNEX) model if modified BDs do not apply. Methods: This was a retrospective analysis using data from the 2‐year interim analysis of the International Ovarian Tumor Analysis (IOTA) Phase‐5 study, in which consecutive patients with at least one adnexal mass were recruited irrespective of subsequent management (conservative or surgery). The main outcome was classification of tumors as benign or malignant, based on histology or on clinical and ultrasound information during 1 year of follow‐up. Multiple imputation was used when outcome based on follow‐up was uncertain according to predefined criteria. Results: A total of 8519 patients were recruited at 36 centers between 2012 and 2015. We excluded patients who were already in follow‐up at recruitment and all patients from 19 centers that did not fulfil our criteria for good‐quality surgical and follow‐up data, leaving 4905 patients across 17 centers for statistical analysis. Overall, 3441 (70%) tumors were benign, 978 (20%) malignant and 486 (10%) uncertain. The modified BDs were applicable in 1798/4905 (37%) tumors, of which 1786 (99.3%) were benign. The two‐step strategy based on ADNEX without CA125 had an area under the receiver‐operating‐characteristics curve (AUC) of 0.94 (95% CI, 0.92–0.96). The risk of malignancy was slightly underestimated, but calibration varied between centers. A sensitivity analysis in which we expanded the definition of uncertain outcome resulted in 1419 (29%) tumors with uncertain outcome and an AUC of the two‐step strategy without CA125 of 0.93 (95% CI, 0.91–0.95). Conclusion: A large proportion of adnexal masses can be classified as benign by the modified BDs. For the remaining masses, the ADNEX model can be used to estimate the risk of malignancy. This two‐step strategy is convenient for clinical use. © 2022 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology. Abstract : Linked article: There is a comment on this article by Jurkovic. Click here to view the Editorial.